Enhancing school safety through psychological support: Key findings and strategies - Souza, Renata Patrícia Pereira (Revista Sistemática, 2024)
A crucial aspect of creating a safe and supportive learning environment is the integration of psychological support to reduce school violence. Research highlights that school violence impacts not only students’ physical safety but also their mental health and emotional development. Effective psychological support can play a pivotal role in preventing and mitigating violent behaviors by addressing underlying emotional difficulties and unresolved trauma. Key strategies include implementing early interventions through school psychologists and counselors, who offer individual and group counseling to help students manage conflicts and intense emotions constructively. Additionally, psychological support programs can improve the school climate through workshops on emotional intelligence, stress management, and social skills, fostering empathy and reducing conflicts. Integrating psychological services with other school resources, such as emotional education programs and violence prevention strategies, is essential. Collaboration among school psychologists, teachers, parents, and administrators ensures a holistic approach to violence prevention, considering all aspects of students’ school lives. The research demonstrates that peer social support significantly mediates the relationship between school victimization and psychological health. Social support acts as a buffer, mitigating the negative effects of violence, and is crucial for students of all genders and ethnicities. Furthermore, family support is identified as a vital moderator, enhancing adolescent mental health despite exposure to violence. Psychological intervention strategies, such as establishing psychological warning systems and prevention mechanisms, are essential in proactively addressing violence. Schools should focus on creating a protective environment and integrating psychological strategies into broader prevention efforts. Continuous mental health education and a safe space for students to express concerns can significantly reduce violent behaviors and support a positive educational atmosphere.